ANALISIS PENGARUH DAYA TARIK DAN KEAHLIAN CELEBRITY ENDORSER TERHADAP KEPUTUSAN PEMBELIAN (STUDI KASUS: VALENTINO ROSSI DALAM IKLAN YAMAHA JUPITER) - Tiwie Tri Andini (2013)
This study was conducted to determine whether the appeal and celebrity endorser expertise influence purchasinng decisions. Respondents in Komplek Marinir Cilandak Timur Jakarta Selatan who has made a purchase Yamaha Jupiter. Obtained a total sample of 100 people. The analysis technique used is multiple regression analysis a hypothesis testing using a significance to the 5% level of confidence. The result showed that the attractiveness and celebrity endorser expertise has a significant influence on purchasing decisions, directly or indirectly.